CANAL CAPACITY IN AREA SUMUR BATU PUMP HOUSE – CENTRAL JAKARTA - Tanjung Rahayu Raswitaningrum; Bagus Kusuma Wardana (International Journal of Civil Engineering and Infrastructure, 2021)
Sumur Batu Pump House is located at Inpeksi Kali Sunter street, Sumur Batu Village, Kemayoran District – Central Jakarta, with coordinates 6°9'41.29" south latitude and 106°52'25.02" east longitude. In the southern part of Sumur Batu Pump House, there is Kodam Complex where there‘s a main canal that flows to the Stone Well Pump House. Around the area of Sumur Batu Pump House, especially Kodam Complex,  flooding still happens frequently, especially during the rainy season. One of the factors causing the flooding is that many canals are sedimented and the dimension of the canals are insufficient to discharge existing rainfall, as well as insufficient pump capacity. By analyzing the canal using Pearson III Log distribution method and Normal Log, and by predicting the highest planned rainfall score in the next 5 years period, which was calculated using past 25 years of rainfall data obtained from Tanjung Priok Rainfall Station, Kemayoran Rainfall Station, and Halim Rainfall Station, which was then calculated by Thiessen method, it was discovered that the rainfall intensity that occurred for a period of 5 years is 167.01 mm in the Normal Log distribution method. The mononobe equation is then used to find the intensity of rain per hour that occurs. Finally, the rain discharge plan can be sought by using rational method. It is then discovered that there are 4 canals (Canals E, H, I, J) that can’t accommodate the occurring rain discharge.